Zulu warriors the battle for the South African frontier - Laband, John 1947- (Yale University Press, 2014)
Toward the end of the 19th century, the British embarked on a concerted series of campaigns in South Africa. Within three years they waged five wars against African states with the intent of destroying their military might and political independence and unifying southern Africa under imperial control. This book tells the story of this cluster of conflicts as a single whole and narrates the experiences of the military outmatched African societies